African mead biotechnology and indigenous knowledge systems in iQhilika process development - Cambray, Garth Anton (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
While the production of mead, a fermented honey beverage, has declined in popularity around the world in recent centuries, a substantial mead industry continues to exist in Africa with an estimated annual production of 1 to 1.7 billion litres. This is largely an 'invisible industry', and has functioned outside the formal economy due to proscription of indigenous beverages during colonial times. The traditional African mead industry is, however, also now under pressure due to the environmental degradation of scarce natural ingredients, urbanisation and loss of indigenous knowledge systems (IKS) and, with time, the beverage will likely follow the declining trend of mead consumption observed elsewhere. An analysis of early reports of African mead production suggested that the Khoi-San, among the earliest inhabitants of the continent, are the originators of the mead making techniques which use fibrous plant materials derived from specific plant species, to facilitate mead fermentation in some way. The Eastern Cape represents a region with a large body of Khoi-San IKS preserved in their descendants among the Afrikaans and Xhosa populations. A survey to establish a baseline of mead-making technology in the Eastern Cape was undertaken, and involved interviewing traditional mead makers across an area of roughly 100 000 km2, showing that the mead, iQhilika(Xhosa) Kari (Khoi-San/Afrikaans), is produced using a very similar process throughout the region. This involves the roots of a Trichodiadema sp. plant (imoela "“ Xhosa, karimoer "“ Afrikaans/Khoi-San), honey, extract of brood and/or pollen and water. Various other fruit sugar sources were also found to be added at times producing seasonal beverages with unique organoleptic properties. A model traditional iQhilika production operation was investigated in order to describe the main features of the process. Biomass immobilised on Trichodiadema root segments was found to be distributed evenly through the profile of the bioreactor resulting in a well mixed fermentation and a productivity of 0.74 g EtOH/l/h. In the initial stages of fermentation, the ethanol yield was highest in the mid-regions of the bioreactor, but with time the regions closer to the surface, which had atmospheric contact had a higher yield. This phenomenon was attributed to aerobic fatty acid synthesis which allowed the yeast close to the surface to function more efficiently despite rising ethanol concentrations. The mead contained 44.25 g/l (7 % volume) ethanol produced in a fermentation time of 43.5 h. Yeast biomass in the traditional process was either immobilised in the form of flocs or attached to the Trichodiadema intonsum support. Electron microscopy revealed that the cells were covered in a layer of extra-cellular polymeric substance apparently assisting the immobilization, and which was populated by a consortium of yeasts and bacteria. Yeasts isolated from iQhilika brewed in two regions separated by 350 km were found to be very closely related Saccharomyces cerevisiae strains as determined by molecular genetic analysis. The traditional beverage was found to contain populations of Lactic acid bacteria (LAB), which are known spoilage organisms in other beverages. Spoilage characteristics of these organisms matched descriptions of spoilage provided by the IKS survey. Other possibly beneficial LAB, which may contribute useful flavour compounds, were also found to be present in the system. The basic functional aspects of the traditional process were used to design a continuous bench-scale tower bioreactor and process development was based on the IKS survey. This consisted of a packed bed bioreactor, consisting of 2 mm3 T. intonsum root segments, immobilising a novel Saccharomyces cerevisiae strain isolated from a traditional batch of iQhilika. The bioreactor performed well with a yield of close to the theoretical maximum and an ethanol productivity of 3.45 g EtOH/l/h. The parameters of the 5.6 l/d bench-scale bioreactor were used to design a full-scale production bioreactor with a planned maximum output of 330 l/d. This bioreactor had a productivity of 0.19 g EtOH/l/h. The organoleptic properties of the product produced were considered by a taste panel to be better than those of the product of the bench-scale tower bioreactor. This research was based on the development of IKS which imposed a number of constraints and obligations on the project to ensure environmental, and social, in addition to financial viability of the scale-up operation. Makana Meadery was established in partnership with Rhodes University as an empowerment company which, in addition to undertaking the commercialisation of the iQhilika process, would also develop methods for the production of scarce ingredients traditionally unsustainably sourced from fragile ecosystems, provide beekeeping training and the manufacture of beehives.
Keywords: Biotechnology; Indigenous peoples -- Africa; Ethnoscience -- Africa; Mead -- Africa; Brewing -- Microbiology; Honeybee; Honey